Análisis de la fuerza isométrica en la propulsión y tracción en slalom en silla de ruedas y su relación con el rendimiento y la clasificación funcional - Reina, R.; Moya, M.; Sarabia, J. M.; Sabido, R. (Revista Internacional de Ciencias del Deporte, 2013)
Athletes with cerebral palsy and acquired cerebral damage are eligible for competition according to the wheelchair slalom classification system. The current trend in the classification systems is to perform an integrated and functional classification based on scientific evidence. Nine national level wheelchair slalom athletes (21,2 ± 4,7 years) from D2, D3 and D4 divisions, as per functional profiles of the Cerebral Palsy International Sports and Recreation Association, took part in the study (5 ? and 4 ?). Participants performed two maximal isometric force tests (propulsion and traction) with their competition wheelchairs in which maximum force (Fmax), average force (Fmed), execution time and time used to reach different Fmax percentages were recorded. In addition, participants carried out two specific performance tests: a 16 m linear sprint with an inversion door after 8 m; and two 4 m linear displacements with a zig-zag round trip. The measured variable was execution time using photocell gates. Significant differences were found between D3 and D4 in propulsion tests for Fmax (p = 0,007) and Fmean (p = 0,002), being this last one higher. Significant statistical differences were found between D2 and D3 in specific performance tests (inversion: p = 0,034 and zig-zag: p = 0,010), being D3 the quickest group. Results show a non-linear relationship between classification divisions and the performance.